Contemporary urban design and planning: Some isms and their exemplary projects - Wróblewski, Wiktor; Zasina, Jakub (Transformations of modern cities: Selected trends and instruments, 2022)
The contemporary face of urban design and planning is heterogeneous. In professional practice and academic discussions different approaches to urban design and planning dovetail or question each other. Consequently, projects representing isms of different principles and methods replenish cities. It seems that current literature lacks the proper review and classification of those isms. Therefore, this chapter aims to present, compare and classify some urban design and planning isms which have emerged and get popularised in the recent decades on both sides of the North Atlantic. The focus is paid particularly on new urbanism, landscape urbanism and do-it-yourself urbanism. The chapter explains the roots behind the isms. It also presents their principles and illustrates them by the completed projects. The analysis resulted in identifying two fundamental axes demarcating the isms doctrinally and methodically. The first axis, STRUCTURE vs PROCESS, distinguishes the isms’ aims, namely the creation of the form or function. The second axis, TACTICS vs STRATEGY, distinguishes the isms’ scale of action, namely small, bottom-up initiatives or large, top-down investments. The chapter concludes that the future face of urban design and planning will be marked by the syncretic hybridisation of principles and methods originating from different current isms.